Thermal Stress Analysis and Control Method for Surface Acoustic Wave Atomizer - Xufeng Xue; Baile Cui; Xianping Chen; Wen Wang; Mingchen Sun; Yong Liang (Sensors, 2023)
To prevent the potential failure of the surface acoustic wave (SAW) atomizer caused by the concentration of thermal stresses, this study investigates the thermal elevation process inherent to the operation of the surface wave atomizer. Subsequently, a method for temperature regulation is proposed. By collecting the temperature rise data of SAW atomizers with water, olive oil, and glycerol at 5/6/7 Watts (W) of power, the temperature curves of the atomizer surface under different conditions are obtained, and the stress changes in the working process are simulated additionally. The results indicate that although the stress generated by surface acoustic wave atomizers varies for different media, there is always a problem of rapid heating during the initial working stage in all cases. To address the above issues, this study analyzed the time when the maximum stress occurred and proposed control methods based on experimental data. The simulation results show that by controlling the driving power within 4 s after the start of atomization, the problem of excessive stress during the heating stage can be avoided. Finally, the feasibility of the control method was verified through a simple power control method (limiting the driving power to 3 W in the first 2 s), proving that this method can effectively reduce the thermal stress during the working process of the atomizer and prevent the atomizer from cracking.